Making waves: Applying systems biology principles in water distribution systems engineering. (1st July 2022) - Abhijith, Gopinathan R.; Ostfeld, Avi
Highlights: Analogy between systems biology and water supply engineering for the first time. Novel strategy for analyzing the changes in delivered drinking water quality. System-level understanding of the reaction mechanisms within water pipes. Multiscale-based modeling inspired by the flux balance analysis concepts. Achieving higher water quality and resource efficiency in water supply management. Abstract: The complexity of modeling water quality variations in water distribution systems (WDS), studied for decades, stems from multiple constraints and variables involved and the complexity of the system behavior. The conventional macroscale-based WDS water quality models are founded on continuum mechanics. In attempts to provide a broad picture of the multi-species interactions, these models overlook the stochasticity corresponding to the reaction mechanisms within the WDS domain. Furthermore, owing to the black-box type modeling adopted in simulating the multi-species interactions, the existing state-of-the-art models have limitations in representing intermediates and/or by-products formation. Accordingly, they remain ineffective in describing the water chemistry-stoichiometric interactions within the WDS domain. Only a radically new modeling approach could overcome the limitations of the macroscale-based approaches and enables analyzing the stochastic WDS mechanisms by keeping the true nature of the system behavior. Stimulated by the metabolic network modeling principles in systems biology, this article outlines the prospect of developing an innovative 'water'bolic network modeling approach to provide a new outlook to the existing WDS water quality modeling research. Graphical abstract: Image, graphical abstract